Triangle Mesh Watermarking and Steganography - Zhou, Hang.; Chen, Kejiang; Ma, Zehua; Wang, Feng.; Zhang, Weiming (Singapore : Springer Nature Singapore : Imprint: Springer, 2023)
This book provides a systematic overview of watermarking and steganography methods for triangle meshes related to computer graphics and security. The significance of this research has been well recognized by the growing body of work on watermarking, steganography and steganalysis of 3D meshes. With the evolution of the CAD industry and real-world end-user applications such as virtual reality (VR) and 3D printing, 3D meshes have attracted world-wide attention. Besides, the flexible data structure of 3D geometry provides enough space to embed secret information, making it ideal for applications such as copyright protection and covert communication. Our goal of the book is to allow readers to systematically understand 3D mesh information hiding technology and its applications as a whole. The book outlines comprehensive techniques, including handcrafted and deep learning-based techniques, digital and physical techniques in the literature and provides standard evaluation metrics for triangle meshes. The up-to-date geometrical deep learning and 3D printing-related algorithms are also covered. Offering a rich blend of ideas and algorithms, the book is up-to-date and self-contained. It is an excellent reference resource for users who are seeking 3D mesh watermarking and steganography algorithms, as well as for graduate students and researchers wanting to grasp the frontiers of triangular mesh processing on data hiding.
1. Introduction -- 2. Watermarking, steganography and steganalysis -- 3. 3D mesh watermakring techniques -- 4. 3D mesh steganography and steganalysis techniques -- 5. Conclusion and Future Work.
Keywords: Data protection; Computer graphics; Cryptography; Data encryption (Computer science).; Data and Information Security; Computer Graphics; Cryptology